73.5k views
1 vote
PLEASEEEE HELPPPPPP!

PLEASEEEE HELPPPPPP!-example-1
User Cody Chang
by
5.8k points

1 Answer

5 votes

Answer:

We conclude that the value of 'a' will be:


a=(x+b^2)/(2)

Hence, option (2) is true.

Explanation:

Given the equation

x = 2a - b²

Let us solve the equation to solve for 'a'


x=2a-b^2

switching sides


2a-b^2=x

Add b² to both sides


2a-b^2+b^2=x+b^2

Simplify


2a=x+b^2

Divide both sides by 2


(2a)/(2)=(x)/(2)+(b^2)/(2)

Simplify


a=(x+b^2)/(2)

Therefore, we conclude that the value of 'a' will be:


a=(x+b^2)/(2)

Hence, option (2) is true.

User Alex Curylo
by
5.3k points